A Design Space for Virtuality-Introduced Internet of Things - Kota Gushima; Tatsuo Nakajima (Future Internet, 2017)
Augmented reality (AR) and virtual reality (VR) technologies have been dramatically expanded in recent years. In the near future, we expect that diverse digital services that employ Internet of Things (IoT) technologies enhanced with AR and VR will become more popular. Advanced information technologies will enable the physical world to be fused with the virtual world. These digital services will be advanced via virtuality, which means that things that do not physically exist make people believe in their existence. We propose a design space for digital services that are enhanced via virtuality based on insights extracted from three case studies that we have developed and from discussions in focus groups that analyze how existing commercial IoT products proposed in a commercial crowdfunding platform, Kickstarter, could be enhanced through virtuality. The derived design space offers three dimensions to design a digital service to fuse IoT technologies with virtuality: (1) Taxonomy of IoT; (2) Visualizing Level, and (3) Virtuality Level. The design space will help IoT-based digital service designers to develop advanced future IoT products that incorporate virtuality.